Children's acceptance of milk with xylitol or sorbitol for dental caries prevention - Castillo Ramon; Coldwell Susan E; Milgrom Peter; Castillo Jorge L; Lazo Rocio (BMC, 2005)
Abstract Background Xylitol, a polyol sugar, has been shown to reduce dental caries when mixed with food or chewing gum. This study examines the taste acceptability of xylitol in milk as a first step toward measuring the effectiveness of xylitol in milk for the reduction of dental caries in a public health program. Methods Three different types of milk (Ultra High Temperature (UHT), powder and evaporated) were tested for acceptability by 75 Peruvian children (25 per milk group, ages 4 to 7 years). Each group evaluated xylitol and sorbitol in one type of milk. In the first phase, each child was presented with a tray of four plastic cups containing 50 ml of milk with 0.021 g/ml xylitol, 0.042 g/ml xylitol, 0.042 g/ml sorbitol or no sugar. Each child was asked to taste the samples in a self-selected order. After tasting each sample, the child placed the milk cup in front of one of three cartoon faces (smile, frown or neutral) representing the child's response to the taste of each sample. In the second phase, the child was asked to rank order the milk samples within each category (smile, frown or neutral). Ranks within categories were then combined to obtain a rank ordering for all the test samples. Results The ranking from best to worst for the samples across categories (UHT, powder, evaporated) was xylitol (0.0.042 g/ml), sorbitol (0.042 g/ml), xylitol (0.021 g/ml) and milk alone (Friedman's ANOVA). Xylitol and sorbitol were preferred over milk alone, and xylitol (0.042 g/ml) was preferred to sorbitol (0.042 g/ml)(p < .05 sign test). Conclusion Milk sweetened with xylitol is well accepted by Peruvian children ages 4-7 years.